From Farms to Cities: Understanding Labor Migration Determinants in Indonesia’s Agricultural Sector During Structural Transformation - Aryo Utomo, Bimo; Darmawan, Arif; Plamadeala, Constantin (Faculty of Social and Political Science, 2025)
This study examines the determinants of labor migration from the agricultural sector in the structural transformation process in Indonesia. Using a panel data regression approach, this study analyzes the effects of several key factors, including provincial minimum wage, agricultural land area, inflation, GDP growth in the agricultural sector, and the proportion of employment in the agricultural sector on labor mobility. The results indicate that these variables exhibit varying influences on the transition of labor from agriculture to other economic sectors. The findings reveal that minimum wage increases tend to limit the absorption of labor in the modern sector, encouraging workers to remain in agriculture. Meanwhile, a reduction in agricultural land area and inflation negatively impact agricultural employment, accelerating labor migration to other sectors. However, GDP growth in agriculture does not significantly affect labor retention in the sector, suggesting that economic expansion in agriculture does not always translate into higher labor absorption. Additionally, the proportion of employment in agriculture significantly influences workforce retention, indicating that job opportunities in the sector play a crucial role in sustaining agricultural labor. These insights provide valuable implications for policymakers in designing strategies to maintain workforce resilience in agriculture while promoting inclusive economic growth in Indonesia.